Water Pressure Data Recording System On Pipes Based On The Internet Of Things Networking - Khoerul - Anwar; Mahmud - Yunus; Eka - Yuniar (AIBPM Publisher, 2023)
Measurement system technology is increasing along with the development of digital technology today. Because of this, currently various kinds of measurement tools can be made in digital versions. Likewise, the technology for measuring water pressure in pipes is also made digitally, although there are still many conventional measurements, for example the flow meter that we usually see in housing in general. The purpose of the system being built is to monitor the water pressure sensor nodes installed in various water sources to ensure sufficient compressive power in an effort to push water up to the customers. Each water pressure sensor node can be monitored from the system dashboard in real time. In this paper, the author offers an IoT-based measurement system for microcontroller technology on a smart pressure meter using a water pressure sensor controlled by the NodeMCU and the pressure bar is calculated then the data is sent to the cloud with the GPRS module, then the results will be displayed on the monitoring system dashboard. The implementation of DWM IoT technology is able to monitor pressure in several PDAM nodes by recording data and display pressure data in graphical form on the DWM IoT dashboard